A Rewiew on Date Rape, Rape Myts and Perception of Gender - Kolburan, Şahide Güliz (The Bulletin of Legal Medicine, 2023)
Date rape is a term that describes sexual assault occurring when the rapist and the victim are in a personal or social relationship. Within this concept, the fact that the perpetrator and the victim have met before or have an ongoing relationship takes the crime of sexual assault out of its context and turns it into discourses aimed at blaming the victim. Such discourses, which almost acquit the aggressor, function to produce social justifications for criminal behavior. Rape is never victim’s fault. This perspective, which is known to be related to rape myths and gender roles, is important in terms of justice, individual rights, and social perspective. Victims of date rape are deprived of seeking social support and social help; they also do not prefer to seek their rights and application to legal processes. In proportion of social acceptance of rape myths, victims internalize the shame about their experience and develop a mechanism that blames themselves, so both the severity of trauma increases and the trauma repair process suffers. The severity of the trauma is closely related to the reaction which is given to this behavior in the social environment where the victim lives. In this review study, the concept of “Date Rape” is explained in the context of the literature and is evaluated in terms of gender roles and rape myths. The aim of this study is to evaluate the concept of date rape in terms of secondary victimization.
Keywords: Date rape; Rape myths; Gender; Sexual assault